The Critical Role and Effects of Patient-Centered Communication in Psychotherapy: A Narrative Review - Niu Y; Sun J; Zhu K; Xu B; Zhang YP; Peng M (Psychology Research and Behavior Management)
Yaohong Niu,1,* Jingbo Sun,2,* Kerun Zhu,1 Bojun Xu,1 Yin-Ping Zhang,3 Min Peng3 1School of Journalism and New Media, Xi’an Jiaotong University, Xi’an, 710049, People’s Republic of China; 2School of Sport Management and Communication, Capital University of Physical Education and Sports, Beijing, 100088, People’s Republic of China; 3Health Science Center, Xi’an Jiaotong University, Xi’an, 710061, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Peng, Health Science Center, Xi’an Jiaotong University, No. 76, Yanta West Road, Xi’an, 710061, People’s Republic of China, Email pengmin2020@stu.xjtu.edu.cn Yin-Ping Zhang, Health Science Center, Xi’an Jiaotong University, No. 76, Yanta West Road, Xi’an, 710061, People’s Republic of China, Email cathyzh@mail.xjtu.edu.cnAbstract: Patient-centered communication has emerged as a fundamental component of effective psychotherapy, significantly influencing the therapeutic process and outcomes. This narrative review examined 53 studies selected from PsycINFO, PubMed, and CINAHL databases published between 2010– 2024, focusing on empirical and theoretical work on patient-centered communication in psychotherapy. A significant portion of this review is dedicated to analyzing the effects of patient-centered communication on therapeutic outcomes. The evidence consistently demonstrates that this approach enhances the therapeutic alliance, improves treatment adherence and engagement, increases patient satisfaction, and leads to better overall mental health outcomes. The review also examines how patient-centered communication is applied across different therapeutic modalities, including cognitive-behavioral therapy, psychodynamic approaches, and group therapy settings. Cultural considerations in patient-centered communication are thoroughly explored, highlighting the importance of adapting communication styles for diverse populations and addressing language barriers and cultural differences. The review discusses the impact of culturally sensitive patient-centered communication on therapeutic outcomes for minority groups, emphasizing its potential to reduce disparities in mental health care. This narrative review also provides valuable insights for mental health professionals, researchers, and policymakers, underscoring the importance of patient-centered communication in advancing the field of psychotherapy and improving mental health care delivery.Keywords: patient-centered communication, psychotherapy, therapeutic alliance, treatment outcomes, cultural competence, mental health care